Determining of critical and dreaded states achieved during metro line supervision - Paquereau, Delphine; Piétrac, Laurent; Niel, Eric; Bouresche, Laurent (22nd Mediterranean Conference on Control and Automation : 16-19 June 2014, 2014)
The research developed here comes within a global approach of a metro line supervision study. Methodology of supervisory control theory is applied to avoid undesirable behaviors during incident situations management and so enforce passengers safety. In this paper, unlike the forbidden state problem, the set of states not to reach is not a given parameter. This set corresponds to safety and controllability constraints: the sets of critical and dreaded states are defined and determined. An example is presented in transport systems area and the developed algorithm is used to identify potentially unsafe situations which do not ensure passengers safety.